Global, Regional, and National Burden of Non-Rheumatic Valvular Heart Diseases in Women: A Systematic Analysis of Global Burden of Disease 1990–2021 - Liu Chenyu; Li Haochao; Chen Pengfei; Chen Mingjian; Zhao Diming; Wang Liqing (Global Heart)
Background: The incidence of non-rheumatic valvular heart diseases (NRVHD) has shown an increasing trend. However, most studies have overlooked the impact of gender on the disease. Female patients, as a specific subgroup, have rarely been discussed independently. It is essential to conduct separate epidemiological studies to understand the latest epidemiological data for female NRVHD patients and to raise awareness among researchers and clinicians. Methods: Data from the Global Burden of Disease (GBD) 2021 database were retrieved to obtain epidemiological data on female NRVHD from both global and regional perspectives, covering 204 countries and territories. Joinpoint regression, age-period-cohort analysis, decomposition, and predictive analyses were employed to further examine the epidemiological data. Results: The incidence of female NRVHD patients has shown a continuous upward trend and is expected to persist in the future, particularly in regions with high and high-middle Socio-Demographic Index (SDI). However, in low and lower-middle SDI regions, patients experience relatively higher Disability-Adjusted Life Years (DALYs) and Years Lived with Disability (YLDs), with a greater number of heart failure cases attributed to NRVHD. Decomposition analysis indicates that the increase in the incidence of NRVHD and its subtypes is primarily driven by population growth and aging. Conclusions: With economic development and population aging, female NRVHD remains a significant healthcare burden for countries worldwide. Low- and middle-SDI regions should implement tertiary prevention strategies to address the impending shift in the spectrum of valvular heart diseases. Further clinical research should focus on female patients as a distinct subgroup of NRVHD, exploring the unique aspects of the disease in this population.